علاقة دافعية الانجاز والثقة بالنفس بدقة التصويب من القفز عالياً بكرة اليد - كاظم، أفراح رحمان (جامعة بابل - كلية التربية الرياضية, 2015)
إن ما يميز لعبة كرة اليد اعتمادها على القدرات العقلية والنفسية بالقدر نفسه الذي تعتمد عليه القدرات البدنية ومن هنا تكمن أهمية البحث في التعرف على الانجاز والثقة بالنفس وعلاقتهما بدقة مهارة التصويب من القفز عالياً لدى لاعبي منتخب جامعة القادسية بكرة اليد للموسم الرياضي (2013م -2014م). إما مشكلة البحث فكانت تتعلق بأهمية العوامل العقلية لدى لاعبي كرة اليد بالإضافة إلى العوامل البدنية والمهارية ودورها في تكامل بناء وإعداد اللاعب ليكون مؤهلا لتحقيق النتائج المتقدمة العلاقة. وقد فرضت الباحثة وجود علاقة ذات دلالة إحصائية بين دافعية الانجاز الرياضي والثقة بالنفس ودقة التصويب من القفز عالياً بكرة اليد لدى إفراد عينة البحث. وقد استخدمت الباحثة المنهج الوصفي نظرا لملائمته طبيعة المشكلة .وبعد إجراء الاختبارات تم معالجة البيانات إحصائيا وقد توصلت الباحثة إلى أهم النتائج وهي ان لاعبي منتخب جامعة القادسية لكرة اليد يتمتعون بدافعية إنجاز وثقة بالنفس عاليين ووجود علاقة ارتباط بين دافعية الإنجاز ودقة التصويب وذلك ما يدعم الحاجة إلى النجاح من خلال دقة التصويب من القفز عاليا لإحراز النقاط. واضافة الى ذلك عدم وجود علاقة ارتباط بين الثقة بالنفس ودقة التصويب من القفز عالياً وذلك لأن الزيادة في الثقة في النفس تؤدي الى الحيلولة دون تحقيق النجاح من خلال دقة التصويب لان الثقة بالنفس كلما زادت ادت الى الوصول باللاعب الى الغرور . ومن أهم التوصيات ضرورة الاهتمام بتطبيق الاختبارات النفسية والمهارية من اجل التعرف على مستوى التقدم في كلا العنصرين النفسي والمهاري .
Depending on the mental and psychological abilities as much as to the physical abilities is what distinguishes the handball game. Out of this, the importance of the research lies in identifying the accomplishment and self-confidence and their relationship to the accuracy of throwing with high jumping among the players of Al-Qadisiyah University team in handball for the season (2013-2014). The research problem was about the importance of mental factors among the players of handball and of the physical and skill factors as well and their roles in the integration of building and preparing the players to be eligible to achieve the relevant advanced results. The researcher hypothesized that there was a statistically significant relationship between the sports achievement motivation and self-confidence with the accuracy of throwing with high jumping in handball among the research participants. The researcher used the descriptive approach due to its suitability to the nature of the problem. After tests were conducted, the data was treated statistically, and the researcher reached to the most important conclusions, which were: the players of Al-Qadisiyah University team in handball had high achievement motivation and self-confidence, and there was a relationship between the achievement motivation and the accuracy of throwing and that is what supports the need to succeed through the accuracy of throwing for scoring. In addition, it was found out that there was no correlation between self-confidence and the accuracy of throwing with high jumping because of the more self-confidence that comes between achieving success through the accuracy of throwing as the more self-confidence leads to make the players' self-conceived. The most important recommendations of the study were: the necessity of implementing the psychological and skill tests in order to identify the level of progress in both psychological and skill elements
Keywords: دافعية الانجاز -- الثقة بالنفس -- دقة التصويب -- كرة اليد